Efficacy and safety of 6 or 8 weeks of simeprevir, daclatasvir, sofosbuvir for HCV genotype 1 infection. Issue 6 (6th February 2018) - Sulkowski, M. S.; Feld, J. J.; Lawitz, E.; Felizarta, F.; Corregidor, A. M.; Khalid, O.; Ghalib, R.; Smith, W. B.; Van Eygen, V.; Luo, D.; Vijgen, L.; Gamil, M.; et al.
Summary: The phase 2, open‐label ACCORDION (ClinicalTrials.gov: NCT02349048) study investigated the efficacy, safety and pharmacokinetics of a 6‐ or 8‐week regimen of simeprevir, daclatasvir and sofosbuvir in treatment‐naïve patients with chronic hepatitis C virus (HCV) genotype (GT) 1 infection and either early‐stage fibrosis or compensated cirrhosis. Patients were assigned to treatment groups according to their fibrosis stage. Early‐stage fibrosis: simeprevir 150 mg, daclatasvir 60 mg, sofosbuvir 400 mg once daily for 6 weeks; compensated cirrhosis: same regimen for 8 weeks. The primary endpoint was sustained virologic response 12 weeks after the end of treatment (SVR12). Safety, tolerability and pharmacokinetics of simeprevir, daclatasvir and sofosbuvir were investigated. Sixty‐eight patients were treated (6‐week group: n = 59; 8‐week group: n = 9). SVR12 was achieved by 86.4% (51/59) of patients with early‐stage fibrosis and by 100% (9/9) of patients with cirrhosis. The main reason for not achieving SVR12 in the 6‐week group was viral relapse (11.9%; 7/59). One patient had on‐treatment failure due to an early withdrawal (lost to follow‐up due to incarceration). One patient with SVR12 in the 6‐week group had a late viral relapse at post‐treatment week 24. No clinically significant drug‐drug interactions were observed. Adverse events were reported in 63.2% of patients (43/68) and were mainly grade 1/2. None of these led to treatment discontinuation. The 3 direct‐acting antiviral regimens of simeprevir, daclatasvir and sofosbuvir were safe and well tolerated in treatment‐naïve, HCV GT1‐infected patients with early‐stage fibrosis or compensated cirrhosis.